Unholy compromise in the Eurozone and how to mend it - Stefano Micossi (WWWforEurope, 2012)
This paper reviews the causes of the ongoing crisis in the eurozone and the policies needed to restore stability in financial markets and reassure a bewildered public. Its main message is that the EU will not overcome the crisis until it has a comprehensive and convincing set of policies in place; able to address simultaneously budgetary discipline and the sovereign debt crisis, the banking crisis, adequate liquidity provision by the ECB and dismal growth.
Keywords: E61; E63; F33; F36; F42; 330; Euro crisis; monetary union; policy coordination